ANALISIS PERKEMBANGAN KONFLIK DI SELAT MALAKA AKIBAT REKLAMASI PANTAI SINGAPURA - Kuntarti, Rita; Putrantono, Asep Hanry; Kurniatun, Endang Sri; Irawan, Adeyaksa (JURNAL DWIJA KUSUMA, 2024)
Singapore did reclamation since 1962. Reclamation is done because the beach area of ​​the land is narrow, for anticipating the growth in population and economic and business considerations. Reclamation conducted in almost all parts of the coast of Singapore has managed to expand its land area. If at the time of independence the size of Singapore only 581 km2, in 2000 the total area of ​​the land has reached 766 km2. The purpose of the thesis writer is to know the situation that occurred today in the Strait of Malacca, to determine the impact that occurs in the presence of reclamation, and to know the solution of Indonesia-Singapore border conflict. In the thesis the author using qualitative methods. Authors make reference source in this thesis are the books, seminars and articles from the internet. The survey results revealed that Singapore's reclamation conducted an impact on the determination of the maritime boundary between Indonesia and Singapore. Reclamation can cause maritime boundary between Indonesia and Singapore shifted to the south. According to international law, this is possible because the maritime boundary between the two countries has not been determined and the possibility of Singapore finished using a new starting point of land reclamation results in the determination of the maritime boundary. While the central part of the maritime boundary established de jure not be shifted because of an agreement on the state border is final and can not be changed. Reclamation which causes a shift in the maritime boundary between Indonesia and Singapore that bring benefits to Singapore because of an area and its territorial sovereignty can be increased. In contrast, Singapore's reclamation bring harm to Indonesia because of the territorial waters and territorial sovereignty is reduced.